1999
DOI: 10.1002/j.1556-6676.1999.tb02452.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Competence and Counselor Training: A National Survey

Abstract: The extent to which practicing professional counselors perceive themselves as multiculturally competent and the basis for their training experiences in multicultural counseling have not been determined. This article reports the results of a survey on practicing professional counselors' perceptions of their multicultural competence and the nature of their pre‐ and in‐service professional preparation in this area. There was no significant difference in self‐perceived multicultural competence between graduates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 23 publications
11
123
4
1
Order By: Relevance
“…In a survey of American Counseling Association (ACA) members, most reported feeling that their level of multicultural training was insufficient (Holcomb-McCoy & Myers, 1999). Holcomb-McCoy and Myers concluded that the current training methods were producing competence in the cognitive domain only, while experiential and emotional domains remained unaffected.…”
Section: Challenges In Training For Multicultural Awarenessmentioning
confidence: 96%
“…In a survey of American Counseling Association (ACA) members, most reported feeling that their level of multicultural training was insufficient (Holcomb-McCoy & Myers, 1999). Holcomb-McCoy and Myers concluded that the current training methods were producing competence in the cognitive domain only, while experiential and emotional domains remained unaffected.…”
Section: Challenges In Training For Multicultural Awarenessmentioning
confidence: 96%
“…Most of these are selfreport (e.g., D'Andrea, Daniels, & Heck, 1991;Holcomb-McCoy & Myers, 1999;LaFromboise et al, 1991;Ponterotto et al, 1996; Sodowsky, Taffe, Gutkin, & Wise, 1994); however, we found one measure that is a -consumer‖-based measure (e.g., Cornelius, Booker, Arthur, Reeves & Morgan, 2004).…”
Section: Existing Measures Related To Cultural Competencementioning
confidence: 67%
“…Holcomb-McCoy (2005), states that "Many variables concerning the multicultural counseling competence of professional counselors have been debated and discussed throughout the recent history of the counseling profession" (p. 414). Additionally, Holcomb-McCoy & Myers (1999) found counselors who addressed multicultural counseling in their training programs had greater cultural competency than those who had not.…”
Section: Multicultural Competencementioning
confidence: 98%